2009
DOI: 10.1073/pnas.0806887106
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear threshold behavior during the loss of Arctic sea ice

Abstract: In light of the rapid recent retreat of Arctic sea ice, a number of studies have discussed the possibility of a critical threshold (or ''tipping point'') beyond which the ice-albedo feedback causes the ice cover to melt away in an irreversible process. The focus has typically been centered on the annual minimum (September) ice cover, which is often seen as particularly susceptible to destabilization by the ice-albedo feedback. Here, we examine the central physical processes associated with the transition from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
302
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 203 publications
(318 citation statements)
references
References 27 publications
16
302
0
Order By: Relevance
“…Hence, even if an ice cover were stable in this simple energybalance model for today's climate, it might well become unstable in a future warmer climate with a smaller ε: In such a climate, the transition to a smaller ice cover could be strongly nonlinear. A similar result, but for a different reason as discussed in Arctic Sea Ice, is also found in more-complex modeling studies (1,9).…”
Section: The Ice-albedo Feedbacksupporting
confidence: 80%
See 1 more Smart Citation
“…Hence, even if an ice cover were stable in this simple energybalance model for today's climate, it might well become unstable in a future warmer climate with a smaller ε: In such a climate, the transition to a smaller ice cover could be strongly nonlinear. A similar result, but for a different reason as discussed in Arctic Sea Ice, is also found in more-complex modeling studies (1,9).…”
Section: The Ice-albedo Feedbacksupporting
confidence: 80%
“…Given that more complex models usually employ more realistic representations of heat transport, it was expected that they might not show the small ice-cap instability. Recently, a number of studies found that it is indeed probable that no such instability exists for the loss of Arctic summer sea ice, whereas an instability might well exist for the transition from a seasonally ice-covered Arctic Ocean to an Arctic Ocean that is virtually free of sea ice throughout the entire year (1,7,9).…”
Section: The Small Ice-cap Instabilitymentioning
confidence: 99%
“…In a study of the forecast skill of a linear empirical model, Lindsay et al (2008) found no skill in predicting detrended data for time scales of three or more months. Finally, the rapid decay in ice area anomalies is also found in climate models (see Armour et al 2011b and references therein) and this is argued to underlie the lack of hysteresis associated with the loss of summer sea ice in both global models and theoretical treatments such as in Eisenman & Wettlaufer (2009). The corpus of these studies led to the general conclusion of rapidly decaying correlations and hence compromised predictability.…”
Section: (D) Discussionmentioning
confidence: 94%
“…The year that the North Pole becomes seasonally ice-free will likely be seen as a 'tipping point' by non-experts. Whilst politically important, several authors argue it is unlikely that such a transition involves an irreversible bifurcation (Eisenman and Wettlaufer 2009;Tietsche et al 2011) (as in Fig. 1a).…”
Section: Summer Sea-ice Lossmentioning
confidence: 99%
“…year-round) ice is more likely to represent a bifurcation (Fig. 1a), where the system can switch rapidly and irreversibly from one state (with seasonal ice) to another (without any) (Eisenman and Wettlaufer 2009). However, the tipping point for year-round ice loss requires around 13°C warming at the North Pole (Winton 2006).…”
Section: Year-round Sea-ice Lossmentioning
confidence: 99%